2008
DOI: 10.3338/kjc.2008.19.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Touch Imprint and Fine Needle Aspiration Cytology of Giant Cell Tumor of Tendon Sheath: A Case Report

Abstract: INTRODUCTIONGiant cell tumors of the tendon sheath (GCTTS) are the second most common lesion of the hand, with simple ganglion cysts being the most common. This tumor was first described by Chassaignac, who referred to it as a "cancer of the tendon sheath". 1 Giant cell tumor of the tendon sheath (GCTTS) is a slowly growing, benign soft tissue tumor. The tumors occur predominantly on the hands and feet. Although the clinical and histopathologic features are well-defined, only a few reports have described the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…2,7 First are the stromal cells or histiocyte-like cells that appear round to fusiform, eccentrically placed nuclei, even chromatin distribution, single micronucleoli and a small to moderate amount of cytoplasm with dispersed individual cells or loosely aggregated sheets. 2,[7][8][9] Binucleation, nuclear groove or intranuclear pseudoinclusion may be illustrated in some cases. 2,8,10 Multinucleated giant cells are another main feature of GCTTS.…”
Section: Plumworasawat S and Jinawath A Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7 First are the stromal cells or histiocyte-like cells that appear round to fusiform, eccentrically placed nuclei, even chromatin distribution, single micronucleoli and a small to moderate amount of cytoplasm with dispersed individual cells or loosely aggregated sheets. 2,[7][8][9] Binucleation, nuclear groove or intranuclear pseudoinclusion may be illustrated in some cases. 2,8,10 Multinucleated giant cells are another main feature of GCTTS.…”
Section: Plumworasawat S and Jinawath A Discussionmentioning
confidence: 99%
“…They usually contain 3 to more than 50 nuclei in each cell with amphophilic cytoplasm. 2,7,9 Other features, advocating GCTTS diagnosis, are hemosiderin-laden macrophages, xanthoma cells and myxoid background. 2,7,9,11 According to these features in those prior studies, almost all findings could be found in our presented case, comprising stromal cells, multinucleated giant cells and hemosiderin-laden macrophages.…”
Section: Plumworasawat S and Jinawath A Discussionmentioning
confidence: 99%